Six new eriophyoid mites (Acari: Eriophyoidea) associated with Ficus spp. (Moraceae) from China - Wang, Guoquan; Wei, Suigai; Yang, Ding (Zootaxa, 2009)
Six new species of the family Eriophyidae associated with the plant genus Ficus (Moraceae) from southern China are described and illustrated in this paper: Colopodacus variegatae sp. nov. infesting F. variegata Bl. var. chlorocarpa (Benth.) King; C. yunnanensis sp. nov. infesting F. benjamina Linn., F. tinctoria Forst. f. var. gibbosa and F. virens Ait. var. sublanceolata (Miq.) Corner; Gammaphytoptus ficus sp. nov. infesting F. variegata Bl. var. chlorocarpa (Benth.) King; Glyptacus microcarpae sp. nov. infesting F. microcarpa Linn., F. hispida Linn., F. benjamina Linn., and F. altissima Bl.; Shevtchenkella hainanensis sp. nov. infesting F. variegata Bl. and Tegonotus hispidae sp. nov. infesting F. hispida Linn.